Ten Crises The Political Economy of China's Development (1949-2020) - Tiejun, Wen (Global University for Sustainability Book Series, 2021)
This open access handbook, Ten Crises systematically traces the economic history of China from 1949 to 2020, unravelling the complex domestic and global factors leading to the cyclical crises identified by WEN and his research team, and examining the corresponding counteracting policies and measures by the government to resolve or defer the crises. The book offers profound insights into China's endeavours and predicaments on the path of modernization, and contemplates opportunities and lessons for the forging of alternative trajectories not only for China but also for the global south: to reconstruct rural communities for integrated cooperation and governance, and to revitalize ecological civilization.